MEDICINAL LUNG INJURY: CLINICAL OBSERVATION - N. A. Karoli (Klinicist, 2014)
Presented clinical case is a classical version of «amiodarone lung» in patient taking inadequate doses of the drug, probably, according to the scenario of acute clinical course